Fra barnets tarv til ligestilling - en queerteoretisk undersøgelse af Folketingets forhandlinger om kunstig befrugtning - Michael Nebeling Petersen (The Royal Danish Library, 2009)
From the best interest of the child to equality - a queer-theoretical analysis of Danish parliamentary debates on artificial insemination.This article presents an examination of the proceedings in the Danish Parliament regarding lesbian and single women's right to medically assisted artificial insemination. In 1996-1997 the Danish Parliament passed legislation banning doctors in Denmark to inseminate women who were not married or in relationship resembling a marriage. This limitation was abrogated by the Parliament in 2005-2006. Through discourse analyses inspired by queer theory I shall examine how such a limitation could be imposed in 1996 and then be abrogated a decade later. In 2006 the pro-discourse used a discursive strategy that equated lesbian parenting with heterosexual parenting, hereby dissolving the destabilizing and queer potential of the lesbian family. The pro-discourse succeeded in uniting several different discourses in the nodal point Equal Rights. However, as my queer analyses will show, the equal rights do not come for free. First of all, the queer identities that cannot exist within heterosexual institutions such as marriage and parenthood are excluded. Secondly, the discursive representation of lesbian parenting is transformed into a symbolic heterosexual formation that supports heteronormative.